Necrophagy in cave environments: ecological pressure due to food scarcity? A case study of necrophagy by a harvestman Discocyrtanus canjinjim Carvalho & Kury, 2017 (Arachnida: Opiliones) preying on an Eidmanacris sp. (Orthoptera: Phalangopsidae) carcass - Sperandei, Vinícius F. (2024)
Cave environments present stable abiotic conditions, including permanent darkness, high humidity, and mild temperatures, while biotic factors reflect simplified ecological networks and energy constraints. Cave invertebrates, primarily detritivores and generalists, demonstrate specific adaptations to these conditions. Predation and necrophagy are critical behaviors shaped by the cave's scarcity of food resources. In this study, we report a rare necrophagy event involving Discocyrtanus canjinjim Carvalho & Kury, 2017 (Arachnida: Opiliones) feeding on a deceased cricket (Eidmanacris sp.) (Orthoptera: Phalangopsidae) in the Ponte de Pedra I Cave, Brazil. This limestone cave features large entrances and supports an oligotrophic system. The event occurred in an aphotic zone, where the harvestman displayed no flee behavior despite external stimuli. The presence of other predatory arachnids suggests potential intra-guild competition. Opiliones in the Cerrado and Caatinga exhibit opportunistic carnivory, consuming various prey taxa, including insects and vertebrates. Necrophagy, intra-guild predation, and cannibalism are behaviors reported in subterranean populations due to limited food availability. Climate change and anthropogenic pressures, such as deforestation and mining, threaten the stability of cave environments. Observations like this contribute to understanding the ecological dynamics within caves, highlighting the importance of preserving these fragile ecosystems.